Effect of Mass Media on Awareness of Abortion Law among Women in Nepal - Dhakal, Krishna; Ghimire, Sudha; Adhikari, Ramesh (Tribhuvan University Journal, 2022)
The government of Nepal has committed to the equitable access of family planning devices/services free of cost; however, nearly a fifth of births are unintended, which ends in abortion. Since 2002, abortion has been legalised in Nepal, but many women are unaware of it. Different studies have shown positive relation between mass media and health related behaviour, its relation with abortion is yet to know. This study aims to investigate the effects of mass media for rising awareness of abortion law among women in Nepal. The study was conducted among 12,862 females of reproductive age group using the secondary data of Nepal Demographic and Health Survey (NDHS), 2016. The finding shows that women reading a newspaper at least once a week were more than two times aware of abortion law than those who did not read [COR = 2.31, CI = 2.01–2.67]. Similarly, regarding the age, women aged 35 or above and exposed to mass media [aOR = 1.26, CI = 1.11–1.43] were more likely to have been aware of abortion law compared to those aged less than 25 years. The study showed a significant role of mass media for rising awareness of abortion law, so, reproductive health program planners and policymakers should emphasise the role of mass media to increase awareness on legal aspects of abortion among women of Nepal